Exercise therapy for preventing physical and psychological trauma in earthquake-prone areas: A systematic review - Eriyono Budi Wijoyo; Mustikasari Mustikasari (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Earthquakes impose both physical injuries and psychological disorders such as post-traumatic stress disorder (PTSD), depression, and anxiety. This study aimed to evaluate the effectiveness of exercise therapy in preventing and managing physical and psychological trauma among populations in these regions. Methods: The protocol was registered in PROSPERO (registration number: CRD420251130734) and followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. A literature search was conducted in PubMed, ScienceDirect, and ProQuest (January 2014–August 2025) using MeSH terms and Boolean operators. Eligible studies included the randomized control trial (RCT), quasi-experimental, cohort, and controlled field trials examining exercise interventions for trauma-related outcomes in earthquake settings. Two reviewers independently screened studies, extracted data, and assessed quality using the PEDro scale. Results: Nine studies met the criteria, covering adolescents, older adults, disaster survivors, and refugees. Interventions ranged from yoga and aerobic training to strengthening and community-based rehabilitation. Exercise therapy consistently improved physical (pain, mobility, function) and psychological outcomes (PTSD, anxiety, depression), but methodological flaws, lack of blinding, concealed allocation, and intention-to-treat analysis limited the evidence to moderate quality. Conclusion: Exercise therapy supports both physical recovery and psychological resilience in earthquake-affected populations, but more high-quality RCTs with standardized protocols are needed to strengthen evidence and inform its integration into disaster management.